Challenging chains to change: Gender equity in agricultural value chain development - Royal Tropical Institute; Agri-ProFocus; International Institute of Rural Reconstruction (Royal Tropical Institute, 2013)
Often efforts to improve value chains miss out half of the population – the female half. How can this be changed? Drawing on dozens of cases, and covering a wide range of crops and livestock products, this book explains how development organisations and private entrepreneurs have found ways to improve the position of women in value chains. In bringing together the fields of gender and value chains, the title offers compelling arguments to improve value chain performance – with both women and men able to enjoy the benefits.